THE IMPACT OF THE WORK ENVIRONMENT ON THE PRODUCTIVITY OF THE PASTRY DEPARTMENT EMPLOYEES AT THE APURVA KEMPINSKI BALI - Harefa, Mega Hernawati; Siboro, Lidia Berliana (Journal of Management Small and Medium Enterprises (SMEs), 2024)
This research aims to analyze the impact of the work environment on employees in the Pastry Department of The Apurva Kempinski, Bali. A good work environment has been recognized as essential in increasing employee productivity. Employee productivity is a critical element in achieving organizational success. Therefore, companies often strive to create a conducive work environment to improve the quality of employee work. The research method used is descriptive and causal, with various data analysis techniques, including correlation tests, determination tests, and linear regression analysis. The analysis results show a robust positive relationship between the work environment and employee productivity, with a correlation coefficient of 0.732. These findings indicate that improving the work environment can positively impact employee productivity. This study provides an essential contribution to understanding the importance of a conducive work environment in increasing employee productivity in the hotel industry. Recommendations are recommended for similar companies to pay attention to and improve the work environment to increase employee productivity. Keywords: Work Environment; Employee Productivity; Hospitality